Identifikasi Keberadaan Intrusi Air Laut pada Kawasan Pemukiman di Sekitar Pesisir Pantai Daerah Desa Sukajaya Lempasing Kecamatan Teluk Pandan - Daniel Radityo; Alviyanda Alviyanda; Happy Christin Natalia; Ahmad Hamdani; Angga Ahya Huseina; Anjar Dwi Asterina Denhi; Rifqi Andi Naufal; Zayadah Zayadah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2020)
Sukajaya Lempasing is one of the villages located in Teluk Pandan District, Pesawaran Regency, Lampung Province. Sukajaya Lempasing Village was chosen as a place for research because of its position on the east coast which is directly adjacent to Lampung Bay, of which its groundwater is suspected to be contaminated by seawater, causing the water to be brackish. Field observation, data collection, as well as lithology and air control are needed to see the geological and hydrogeological conditions of this area. Based on the physical and chemical parameters, the well of Hamlet 7 has groundwater and there is no indication of sea water intrusion because the area is very close to hills which may become a catchment area so that groundwater flows out to sea with high pressure. Based on the salinity, TDS, and conductivity values ​​obtained, the well that experienced seawater intrusion was the AJR3 well because it is located closest to the coastline and is supported by an alluvial sediment aquifer that has moderate to high aquifer productivity. The quality of water based on physical parameter data from wells in Hamlet 1, Hamlet 7 and sample AJR4 Hamlet 3 is classified as clean and suitable for daily use. The lithology in the form of alluvial deposits allows seawater intrusion, especially in areas close to the shoreline such as the AJR3 well.